Modelling the maximum potential of nitrogen deposition and requirements of lysine for broilers - De Paula Dorigam, Juliano Cesar [UNESP]; Sakomura, Nilva Kazue [UNESP]; Da Silva, Edney Pereira [UNESP]; Kochenborger Fernandes, Joao Batista [UNESP] (Csiro Publishing, 2014)
This study aimed to develop a dynamic model to estimate lysine (Lys) requirements based on the maximum theoretical potential of nitrogen deposition (NDmaxT) and metabolic bodyweight (MBW) of growing broilers. Three N balance trials were conducted (6-21, 22-37 and 38-53 days of age) at average ages of 14, 30 and 46 days, respectively, with 36 male broilers (Cobb 500) used in each trial. In each trial, the NDmaxT was estimated by exponential model fitting of daily N intake as a function of daily N deposition for the average age. The N deposition was obtained by application of the N balance technique. To model the NDmaxT in relation to MBW, the mean and standard deviation of NDmaxT was used to generate a new population. The critical exponential model was fitted to estimate the daily NDmaxT, resulting in the following model: NDmaxT = 1677 + (-1677 + 13810 x MBW) x (0.151(MBW)). The daily NDmaxT data so generated were used in the Goettingen model to calculate the daily Lys requirements for N retention response. Modelling of Lys requirements resulted in greater than recommended values, with an average difference of 1.05 times the recommendation of the management guide for the studied strain. According to the results obtained from this simulation, the model provided consistent estimates of Lys requirements and may enable nutritionists to provide nutritional strategies to optimise production of broilers based on the MBW.
Keywords: Gompertz function; maintenance; maturity; nitrogen retention